Cancer Disparities in Rural Appalachia: Incidence, Early Detection, and Survivorship. Issue 4 (7th September 2016) - Yao, Nengliang; Alcalá, Héctor E.; Anderson, Roger; Balkrishnan, Rajesh
Abstract: Purpose: To document cancer‐related health disparities in Appalachia. Methods: The current study investigated disparities in cancer incidence, mortality, and staging between rural Appalachians and those living outside of rural Appalachia. To accomplish this, mortality data for the United States from 1969 to 2011 were obtained from the National Center for Health Statistics (NCHS) using SEER * Stat. These data were used to compare trends in mortality between rural Appalachians, urban Appalachians, rural non‐Appalachians, and urban non‐Appalachians. Cancer incidence trends, staging, and survivorship data were compared across regions using the SEER‐18 Program, which represented 28% of the US population and includes 2 Appalachian states: Georgia and Kentucky. Results: Cancer mortality rates declined in all regions, but disparities remained such that rural Appalachia has the highest incidence, while urban non‐Appalachia has the lowest. In all but 1 state, rural Appalachians had higher cancer mortality rates than urban non‐Appalachians. Cancer incidence declined for all regions except rural Appalachia. Rural Appalachians had lower rates of early stage breast cancer diagnoses than their urban non‐Appalachian counterparts. Finally, rural Appalachians had lower 3‐ and 5‐year survival rates than their urban non‐Appalachian counterparts. Conclusions: Rural Appalachians are faced with poorer cancer‐related health outcomes across the continuum of cancer care. A systematic effort is needed to reduce the burden of cancer for rural Appalachia. Additional research should explore reasons for the disparities that were observed.